Veículo de sonhos e ilusões: a Revista Americana e a circulação de representações de pan-americanismo (1909-1919) - Caprara, Larissa Milanezi Fabriz (2018)
This doctorate thesis explores the publication Revista Americana, sponsored by the Ministry of Foreign Affairs, as a space of public opinion and interpretative community carrier of a set of standards which allowed the publication of articles. It released on a non-continuous basis between the years of 1909 and 1919 and became a field to disseminate several aspects of politics, culture and history of Brazil and others southAmerican republics. It aimed to understand its implicit and explicit goals, as well as analyze the role expected from the diplomatic corps in the intention to allow a panamericanism project. We assumed that the Revista was a strategic instrument used by Itamaraty to think and promote the bringing together between Brazil and South America. In addition, from reading the issues off the publication, explored which would be the position of the Brazilian diplomacy in the dissemination of a possible leader of the continent. Also, identified the main representations discussed about the concerns of the American continent and its possible solutions. The intellectuals were not only Brazilians, but also native from other countries of the continent. Analyzed which representation of future were supported at the periodic aiming to symbolize Brazil as a pacific and civilized country, as well as of American continent as modern and solidary relations among the nations. We based our investigation in the concepts of representation, circulation, appropriation and cultural practice of Chartier; intellectuals of Sirinelli and cultural diplomacy of Ribeiro (1989). Our conclusions indicate that those intellectuals appreciated the elements of a cultural diplomacy, through a pan-american rhetoric, which should be appropriated in the constitution of new identities, characterized by its own qualities. The pan-americanism, designed in this direction, underlain the existence of a generation of intellectuals who have published projects of future that represented America not only as a space, but above all, as a sentiment.